Proyecto de introducción y comercialización de la franquicia coco-express en el mercado chileno - Aguilar Romero, Andrea Leonor (2009)
The present crisis by which the world-wide economy faces, promotes to look for new alternatives to us of businesses, where the investment does not require a high percentage of money and in addition it has to be profitable. Also due to the crisis we must become aware and try to help other countries. This project looks for increase relations between the countries of Ecuador and Chile, since the Chilean market is one of the most developed in Latin America with possibilities from expansion inside and abroad. In addition the lack to culture of the fruit, the Coco, motivates to take something to us new and simple to a market with great possibilities of success. This project directly contemplates the acquisition of the Coco-Express franchisee of Mexico, which provides us with all the raw material and it leaves us free of election as far as the acquisition of coco, thus within the project includes an importation process to the Chilean market this cause an increase of the 19% in our costs, despite of this, it is not a negative aspect for the decision making, because since the first year of operations we will have a positive flow, considering a loan to initiate the project.